Genetic monitoring tools for radon pollution research - Biyasheva Zarema; Zaripova Yuliya; Onalbek Diana; Dyachkov Vyacheslav (BIO Web of Conferences, 2024)
A critical target for ionizing radiation is DNA that damage to a cell. Thus, when dealing with the general irradiation of the body, we observe the diverse effects of radiation. As a result of irradiation, somatic cells retain the ability to reproduce, but can give rise to the growth of a clone of altered cells, leading to a malignant neoplasm. The manifestation of ionizing radiation on germ cells can lead to prolonged effects, morphological changes and hereditary diseases. It is quite difficult to study the genetic consequences of radiation on patients due to the difficulties of compiling or selecting comparable control groups or samples and maintaining their representativeness. On the solutions to this problem is to simulate the genetic effects of irradiation on model objects, in our case, this is Drosophila melanogaster. The genetic effects of alpha radiation are main manifested in the morphology form of the wing, thorax and antenna morphoses. However, alpha particles very often cause the development of colored tumors, which have been allied melanomas. Genotoxic, mutagenic and carcinogenic effects of α-radiation were detected in the test systems of the gene white (white eyes), linked X chromosomes and Basc (Me-5).